2020
DOI: 10.1186/s13027-020-0277-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of hepatocellular carcinoma with hepatitis B virus among patients on Nucleos(t) ide analog therapy

Abstract: Background: The clinical manifestation of hepatocellular carcinoma (HCC) with hepatitis B virus (HBV) varies significantly between patients treated with or without nucleos(t) ide analog (NUC) therapy. To have a better understanding of HCC with HBV, we compared the clinical features of patients with HCC receiving or not receiving NUC therapy. Methods: We retrospectively reviewed the medical records of 76 patients with HBV-caused HCC who received treatment at the Hunan Provincial Peoples' Hospital starting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…Some HCC prediction models have also been created in patients undergoing treatment with NAs 30 , 31 and the pre-treatment viral loads were not found to be as crucial as those in NA-naïve patients. Underlying liver cirrhosis was reported to be the most critical determinant of HCC 32 , which is consistent with the results of the present study. The reported annual incidence of HCC was 0.3–1.2% in non-cirrhotic CHB patients and 1.8–6.0% in cirrhotic CHB patients undergoing NA therapy 33 .…”
Section: Discussionsupporting
confidence: 93%
“…Some HCC prediction models have also been created in patients undergoing treatment with NAs 30 , 31 and the pre-treatment viral loads were not found to be as crucial as those in NA-naïve patients. Underlying liver cirrhosis was reported to be the most critical determinant of HCC 32 , which is consistent with the results of the present study. The reported annual incidence of HCC was 0.3–1.2% in non-cirrhotic CHB patients and 1.8–6.0% in cirrhotic CHB patients undergoing NA therapy 33 .…”
Section: Discussionsupporting
confidence: 93%
“…This may suggest that treatment with nucleoside or NA in some patients does not sufficiently suppress carcinogenesis. A retro-spective study by Liu indicated that nucleotide or nucleoside analogue therapy was associated with milder symptoms, fewer and smaller neoplastic lesions on imaging tests, and lower incidence of portal vein tumour thrombosis [7]. Our study also showed that patients successfully treated with antiviral agents and diagnosed with HCC had lower AFP levels, as well as fewer and smaller tumours.…”
Section: Discussionsupporting
confidence: 65%
“…These factors significantly add to the clinical complexity of such patients and increase the difficulty of clinical management. Even more problematic is the fact that there is currently no effective treatment for NASH-related hepatocellular carcinoma (HCC) [ 4 ]. However, the factors influencing the progression from NAFLD to NASH and even to HCC are unclear; although, multiple hypotheses have been proposed, including lipotoxicity, oxidative stress, and proinflammatory mediators [ 5 ].…”
Section: Introductionmentioning
confidence: 99%